(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This study explores the cultural and artistic significance of Turkish ceramic vases, focusing on diplomatic gifts presented to Kazakhstan. Addressing a knowledge gap in the comparative analysis of Iznik and Kutahya ceramic traditions, the research examines three vases from the Presidential Center of the Republic of Kazakhstan’s museum collection. Employing qualitative methods, including artifact analysis and historical context evaluation, the study highlights the evolution of Turkish ceramic techniques and motifs. Findings reveal the interplay of tradition and innovation in Kutahya ceramics, marked by intricate plant patterns and symbolic designs. The results underscore the vases’ dual role as artistic masterpieces and cultural diplomacy tools, enhancing cross-cultural understanding. These insights contribute to the broader discourse on material culture’s role in international relations.